If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(1-x)=3x=-2(x+1)
We move all terms to the left:
4(1-x)-(3x)=0
We add all the numbers together, and all the variables
4(-1x+1)-3x=0
We add all the numbers together, and all the variables
-3x+4(-1x+1)=0
We multiply parentheses
-3x-4x+4=0
We add all the numbers together, and all the variables
-7x+4=0
We move all terms containing x to the left, all other terms to the right
-7x=-4
x=-4/-7
x=4/7
| 3d+2d+6=-15 | | 68+(3x+1)=180 | | -u+19-16u=-19u-9 | | 4m-5+2m=43 | | x+x+x=42 | | 10+2x=45 | | 4r+8+5=−15−3r | | 19.5=39.5+x | | 17r=22+18r | | 63+(3x+1)=180 | | 3h–5=12 | | 16b-18=15b-3 | | 3(c-2)=6 | | 7x-19=2x+11 | | 15.50x+7=100 | | 10+9q=7+8q+20 | | -17-3(2x+13)=+24= | | 9k+8=4+10k | | 7w=18+5w | | p+2=-1 | | 3b+9=b-7 | | 3x(2x+5)-4(x+3)=2x+3 | | -10+8u=9u | | x+51+2x=90 | | 7x-14=4x-17 | | 9q-1-1=-2-5q | | Y=-x²+2x+5 | | 1+v=3 | | 120=12v | | 32-4m=52 | | –6x+8=-5x+5 | | 7=2s |